2019
DOI: 10.1186/s13033-019-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and associated factors among the elderly in Vietnam: a cross-sectional study

Abstract: Background Dementia poses a serious threat to the wellbeing of the elderly. In the context of the rapidly ageing population of Vietnam however, little is known about the prevalence of symptoms and other related factors. This study aims to detect the prevalence of cognitive symptoms of dementia in the elderly in Vietnam as well as other associated factors. Methods A cross-sectional study was conducted over a period of six communes at the Northern, Central and Southern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 6 publications
0
27
0
1
Order By: Relevance
“…In some previous studies, impaired cognition was identified as a predictor of FoF [4,5,12], while in others, no association between cognitive impairment and FoF was observed [13]. In addition, the proportion of Vietnamese elderly who had cognitive symptoms of dementia was recently reported to be high at 46.4% [14]. As there have been limited large-scale population studies investigating FoF as well as the relationship between FoF and cognitive impairment in Vietnam, it is crucial to obtain a clearer understanding about this association in a large communitybased sample.…”
Section: Introductionmentioning
confidence: 97%
“…In some previous studies, impaired cognition was identified as a predictor of FoF [4,5,12], while in others, no association between cognitive impairment and FoF was observed [13]. In addition, the proportion of Vietnamese elderly who had cognitive symptoms of dementia was recently reported to be high at 46.4% [14]. As there have been limited large-scale population studies investigating FoF as well as the relationship between FoF and cognitive impairment in Vietnam, it is crucial to obtain a clearer understanding about this association in a large communitybased sample.…”
Section: Introductionmentioning
confidence: 97%
“…Hence, the present study challenges the validity of the clinical assessment of uneducated/illiterate individuals. It also raises the question whether the high prevalence of dementia in older uneducated/illiterate individuals that is often found in population-based epidemiological studies reflects actual deficits, or is an artifact resulting from the inappropriateness of these tests for this population, thus leading to false-positive results on cognitive screening tests which are used as a reference standard for a dementia diagnosis (Bich et al, 2019;Goudsmit et al, 2020). Finally, our approach may provide a model for researchers in other cultural contexts to explore relevant factors for the neuropsychological assessment of uneducated/illiterate older individuals in their own countries.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the prevalence of severe cognitive impairment, MMSE score 0–23 was used as the criterion to detect dementia and had sensitivity of 0.89 (95% CI, 0.85 to 0.92) and specificity of 0.89 (95% CI, 0.85 to 0.93) [ 26 ]. Using the same criterion of MMSE 0–23, but with some differences in methodologies and study populations, other studies in Vietnam reported severe cognitive impairment prevalence rates of 29–48% [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies mainly investigated epidemiological aspects of cognitive impairment. The previous Vietnam reports showed the prevalence of cognitive impairment ranged from 29% to 48% [ 22 , 23 , 24 ]. However, a lack of study included mild cognitive impairment (MCI), an early stage of dementia.…”
Section: Introductionmentioning
confidence: 99%